A Systematic Review and Meta-Analysis on Neural Adaptations Following Blood Flow Restriction Training: What We Know and What We Don't Know - Centner, Christoph; Lauber, Benedikt (Frontiers in Physiology, 2020)
Objective To summarize the existing evidence on the long-term effects of low-load (LL) blood flow restricted (BFR) exercise on neural markers including both central and peripheral adaptations. Methods A systematic review and meta-analysis was conducted according to the PRISMA guidelines. The literature search was performed independently by two reviewers in the following electronic databases: PubMed, Web of Science, Scopus and CENTRAL. The systematic review included long-term trials investigating the effects of LL-BFR training in healthy subjects and compared theses effects to either LL or high-load (HL) training without blood flow restriction. Results From a total of N = 4499 studies, N = 10 studies were included in the qualitative synthesis and N = 4 studies in a meta-analysis. The findings indicated that LL-BFR resulted in enhanced levels of muscle excitation compared to LL training with pooled effect sizes of 0.87 (95% CI: 0.38-1.36). Compared to HL training, LL-BFR was muscle excitation was reported as either similar or slightly lower. Differences between central activation between LL-BFR and LL or HL are less clear. Conclusion The summarized effects in this systematic review and meta-analysis highlight that BFR training facilitates neural adaptations following LL training, although differences to conventional HL training are less evident. Future research is urgently needed to identify neural alterations following long-term blood flow restricted exercise.